Козакознавство в інтелектуальних студіях української діаспори Австралії у другій половині ХХ ст. - Музичко, О. (Чорноморська минувшина, 2023)
Метою цієї статті є виявлення особливостей функціонування традиції усвідомлення козаків як надважливого архетипу української історії серед донедавна наймолодшої великої української діаспори – австралійської. Завданнями статті є окреслення кола осіб, що згадували про козаків, мотивації, обставини та напрями їх діяльності. Зроблено висновок, що на тлі доробку українських гуманітаріїв, поетів, письменників. митців Канади, США, Західної Європи козакознавство Австралії розвивалось у наздоганяючому темпі, що було зумовлено відносною молодістю діаспори на п’ятому континенті. Більшість зі згаданих персонажів розвивали в Австралії свій попередній доробок (передусім, йдеться про Івана Рибчина). Деякі з вчених, що мали потенціал для відповідних студій (С. Наріжний, Є. Завалинський) з різних причин не виявили активності. Проте, сама наявність козакознавчого сліду у діяльності австралійської інтелігенції промовисто свідчить про потенціал козацької ідеї для консолідації українців. Найоригінальніший доробок серед австралійських вчених належить О. Зибачинського, який зумів включити козацтво у широких історіософський контекст. Заслугою І. Рибчина був аналіз феномену козацтва у психологічному контексті. Він же піддав феномен козацтва більш об’єктивному, а водночас неоконсервативному аналізу. Але у дискурсі австралійської діаспори, як, втім, й інших діаспор, переважав неонародницький та неоромантичний погляд на козацтво. Безумовно, актуальними в умовах нинішньої російської загрози є численні зауваження австралійських українців про націєтворчу діяльність козаків, боротьбу їх проти російського імперіалізму. Загалом, австралійські козакознавчі студії продемонстрували оригінальний синтез міждисциплінарності. The purpose of this article is to investigate how Ukrainians in Australia perceived the Cossacks and popularized knowledge about the Cossacks. The tasks of the article are to write about those persons who mentioned the Cossacks, what they wanted, the circumstances and directions of their activities. The sources for writing the article are materials from the periodical press of the Ukrainian Australian diaspora, some archival materials, works of representatives of the Ukrainian diaspora, articles about their activities in the memoir direction (memoirs, obituaries). In historiography, there is no statement of the question that is the topic of consideration of our article. However, individual comments are contained in personal articles about some of the heroes of our article. It is also worth noting as a historiographical base the articles devoted to the general development of Ukrainian studies (Ukrainian studies) in Australia It was concluded that against the background of the work of Ukrainian humanitarians, poets, writers. artists of Canada, the USA, and Western Europe, Cossack studies in Australia developed at a catch-up pace, which was due to the relative youth of the diaspora on the fifth continent. Most of the mentioned characters developed their previous work in Australia (first of all, we are talking about Ivan Rybchyn). Some of the scientists who had the potential for relevant studies (S. Narizhnyi, E. Zavalynskyi) did not show activity for various reasons. However, the very presence of a trace of Cossack studies in the activities of the Australian intelligentsia eloquently testifies to the potential of the Cossack idea for the consolidation of Ukrainians. The most original work among Australian scientists belongs to O. Zybachynskyi, who managed to include the Cossacks in a broad historiosophical context. The merit of I. Rybchyn was the analysis of the phenomenon of Cossacks in a psychological context. He also subjected the phenomenon of Cossacks to a more objective and at the same time neoconservative analysis. But in the discourse of the Australian diaspora, as well as other diasporas, a neo-populist and neo-romantic view of the Cossacks prevailed. Undoubtedly, the numerous remarks of Australian Ukrainians about the nation-building activities of the Cossacks and their struggle against Russian imperialism are relevant in the conditions of the current Russian threat. In general, Australian Cossack studies have demonstrated an original synthesis of interdisciplinarity.